Distribution of lithium in doped nuclear pores of polyethylene terephthalate by neutron depth profiling. Issue 3 (3rd March 2020) - Ceccio, G.; Horák, P.; Cannavó, A.; Torrisi, A.; Hnatowicz, V.; Vacík, J.
Abstract : In this paper, doping of porous polyethylene terephthalate membrane using Li-based solution is described and analyzed by nuclear analytic methods. In recent years, the polymeric porous membranes have been studied as advanced battery separators in various applications, such as portable electronic devices or electric vehicles. Apart from mechanical stability, the separators also provide electrical separation and ionic transport between the electrodes during charging and discharging processes. For application of the membranes, it is important to follow the Li distribution in the separator material over time. In this work, the distribution of Li in the porous PET foils, adepts for Li ion battery separators, was analyzed by Neutron Depth Profiling and the 3D shape of the etched pores by Ion Transmission Spectroscopy. The data obtained show that Li can be incorporated, in a passive way in the micropores in large quantities, but its amount is still limited and does not depend on time of doping. Here, the first data are presented.